2006
DOI: 10.1016/j.amjhyper.2006.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Is a Determinant of Metabolic Syndrome in a Population-Based Study

Abstract: Abdominal obesity is the main determinant of uric acid variance. An increment of 1 SD in serum uric acid levels are associated in both sexes with a 35% higher MS likelihood, independent of 10 risk factors related to MS. After adjustment for waist girth, a more modest but significant likelihood persists, which suggests that serum uric acid is a determinant of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
123
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(148 citation statements)
references
References 27 publications
19
123
1
5
Order By: Relevance
“…19 However, our study did not find significant interactions between uric acid status and BMI after stratified analysis. A previous study has found the strongest association between uric acid and SBP in the lowest quintiles of fasting glucose, 21 although we did not observe an interaction between fasting glucose and uric acid in our study. A prospective investigation of SUA and the risk of diabetes suggested a positive association between the plasma concentration of uric acid and the incidence of type 2 diabetes in Chinese individuals.…”
Section: Discussioncontrasting
confidence: 93%
“…19 However, our study did not find significant interactions between uric acid status and BMI after stratified analysis. A previous study has found the strongest association between uric acid and SBP in the lowest quintiles of fasting glucose, 21 although we did not observe an interaction between fasting glucose and uric acid in our study. A prospective investigation of SUA and the risk of diabetes suggested a positive association between the plasma concentration of uric acid and the incidence of type 2 diabetes in Chinese individuals.…”
Section: Discussioncontrasting
confidence: 93%
“…In general, our data agree with several cross-sectional studies from different populations that established an association between SUA and MS 2,26 , and with a Brazilian study that included 352 white male individuals from high social class 27 and an observational study that evaluated 756 individuals (369 men) from a convenience sample 12 .…”
Section: Discussionsupporting
confidence: 79%
“…The association between serum uric acid (SUA) and cardiovascular (CV) diseases such as hypertension 1 , metabolic syndrome (MS) 2 , coronary and cerebral vascular diseases 3,4 has been reported in several epidemiologic studies. However, SUA has not been considered an independent cardiovascular risk factor, but only an additional factor associated with CV diseases due to the presence of other conditions such as obesity, dyslipidemia, hypertension, use of diuretics or insulin resistance 5 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ORs for metabolic syndrome increase with the gender-specific quartiles of uric acid levels after adjusting for age, total cholesterol and smoking status in Japanese adults. 29 In a population-based study, Onat et al 30 have shown that the OR of metabolic syndrome is 1.89 using the top-versus-bottom tertile of uric acid level adjusting for possible confounders. In addition, uric acid is independently correlated with number of metabolic syndrome components.…”
Section: Discussionmentioning
confidence: 99%